A novel experimental method for determining the eigen-axes angle of MEMS ring gyroscope. (August 2019) - Wang, Jin; Chen, Zhiyong; Zhang, Rong; Xing, Bowen
Abstract: MEMS ring gyroscope with sensitive structural errors has frequency splitting in the working modes and the eigen-axes are no longer located at any arbitrary position. Among the imperfection, the fourth harmonic distribution components of the mass and Young's modulus have the most significant influence on the frequency split. In order to determine the position angle of the defects, the frequency response characteristics at the sense electrodes of the ring structure were analysed, and a calculate method to ascertain the eigen-axis position was found by using the frequency response parameters. To verify the validity of this method, a finite element model was established, and the harmonic response was analysed. The simulation results show that the relative error is about 8%. This method was applied in a multi-ring eigen-axes experiment, the harmonic response under different drive and sense electrodes combinations were tested. The average of the calculated angle is 43.3050°, and the standard deviation is 0.8940° which shows the consistency of the calculated values. This method provides a support for the modification of ring structure errors.